High Performing Gas Diffusion Biocathode for Microbial Fuel Cells Using Acidophilic Iron Oxidizing Bacteria - Izadi, Paniz; Fontmorin, Jean-Marie; Fernández, Luis F. L.; Cheng, Shaoan; Head, Ian; Yu, Eileen H. (Frontiers in Energy Research, 2019)
The development of a sustainable catalyst for the oxygen reduction reaction is still a major bottleneck for the scale-up and commercialisation of Microbial Fuel Cells (MFCs). In this work, we have studied the utilisation of iron-oxidising bacteria (IOB) enriched from natural environment and Fe2+ in MFCs equipped with gas diffusion electrodes (GDEs) as an alternative to traditional Pt-based catalysts. In half-cells systems, the oxidation of Fe2+ into Fe3+ by IOB and its regeneration at the cathode produced constant current densities close to 2 A m-2 for more than 45 days. In MFCs operated in batch mode, significant pH changes in both compartment led to the instability of the system. However, when operated in continuous mode, pH remained stable in both compartments and MFCs produced maximum power densities of 1.1 W m-2 were then reached, compared to 0.5 W m-2 for MFCs equipped with Pt catalyst. Diffusion of oxygen through the GDEs improved mass transport and the performance of the MFCs, and avoided the utilisation of costly aeration system. This IOB GDE system also provides a reproducible and fast start-up for biocathode for MFCs.